Nonnutritive Sucking Treatment With Removable Orthodontic Appliances - Hillda Herawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Oral habits are habits related to muscle contractions. Oral habit, one of which is nonnutritive sucking (finger sucking), is the first step for children to regulate emotional abilities, relax and focus effects, provide comfort and a sense of security for children for example when feeling tired, bored, afraid and sad. Almost 100% of normal infants will experience the nonnutritive sucking phase until the age of 2-3 years and 20% until the age of 3 years. If the habit continues beyond the age of 3.5 years, it will lead to bad oral habits, which is a repetitive behavior that can cause abnormalities in the teeth and supporting tissues. This bad oral habit can cause changes in the orofacial system, and its manifestations are influenced by factors such as duration, frequency and intensity. Case: A 5-year-old girl came to RSGM escorted by her mother with complaints of having a habit of sucking the middle finger and ring finger on the left and the front teeth bite looks open, and premature loss of tooth 74. Case Management: the patient was given a removable orthodontic device using palatal cribs mounted on the upper jaw and mandibular space maintainer due to tooth 74 loss. Discussions: after observation which was carried out once a week for 10 times within ± 3 months, there were clinical changes, namely overjet 3 mm to 2 mm, open bite 2 mm to 0.5 mm, the lump on the left middle finger thinned and the patient no longer sucked the finger Conclusion: : the success of the treatment is the result of good cooperation between the doctor and the patient and the patient's parents, as well as early treatment of bad oral habit cases. The use of palatal cribs in this case proved effective in controlling finger suck.